Survival following lung transplantation: A population‐based nested case‐control study. Issue 5 (27th February 2022) - Iguidbashian, John; Cotton, Jake; King, Robert W.; Carroll, Adam M.; Gergen, Anna K.; Meguid, Robert A.; Fullerton, David A.; Suarez‐Pierre, Alejandro
Abstract: Background: Lung transplantation is the mainstay of treatment for patients with end‐stage respiratory failure. This study sought to evaluate survival following transplantation compared to the general population and quantify standardized mortality ratios (SMRs) using a nested case‐control study design. Methods: Control subjects were nonhospitalized inhabitants of the United States identified through the National Longitudinal Mortality Study. Case subjects were adults who underwent lung transplantation between 1990 and 2007 and identified through the Organ Procurement and Transplantation Network. Propensity‐matching (5:1, nearest neighbor, caliper = 0.1) was utilized to identify suitable control subjects based on age, sex, race, and location of residency. The primary study endpoint was 10‐year survival. Results: About 14, 977 lung transplant recipients were matched to 74, 885 nonhospitalized US residents. The 10‐year survival rate of lung transplant recipients was 28% (95% confidence interval [CI] = 27%–29%). The population expected mortality rate was 19 deaths/100 person‐years while the observed ratio was 104 deaths/100 person‐years (SMR = 5.39, 95% CI = 5.35–5.43). The largest discrepancies between observed and expected mortality rates were in females (SMR = 5.97), Hispanic (SMR = 10.70), and single lung recipients (SMR = 5.92). SMRs declined over time (1990–1995 = 5.79, 1996–2000 = 5.64, and 2001–2007 = 5.10). Standardized mortality peaks in the first year after transplant and decreases steadily over time. Conclusions: Lung transplant recipients experience a fivefold higher SMR compared to the nonhospitalized population. Long‐term mortality rates have experienced consistent decline over time.